Evaluating the effectiveness of case-based learning in designing basic leadership training: a systematic literature review - Asyifa, Mega; Tarjiah, Indina; Utomo, Erry (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Technological advances and the increasing complexity of challenges in the world of work demand more effective and contextual leadership training designs. This study aims to explore the characteristics of the included study, the effectiveness of Case-Based Learning (CBL) in improving learning outcomes in basic leadership training, as well as the factors that affect the success of its implementation. Using the PRISMA approach, articles that met the inclusion criteria were systematically analyzed from the ScienceDirect database. The results showed that although many studies supported the effectiveness of CBL in improving training outcomes, there was a variation in findings that pointed to the need for further research to understand the contextual factors that influence its success. Evidence shows that CBL is effective in developing leadership skills, teamwork, and management abilities. However, elements such as organizational culture, participant characteristics, and implementation methods can affect the results achieved. Training design that includes simulation, feedback, collaboration, as well as gender inclusivity plays an important role in the successful implementation of CBL. This study emphasizes the need for more in-depth studies to identify specific variables that affect the effectiveness of CBL in basic leadership training. These findings provide valuable insights for future leadership training program designers and encourage further exploration of CBL success factors in various contexts.